Substitute
, so that
. Part of the integrand reduces to
![16 - x^2 = 16 - (4\sin(y))^2 = 16 - 16 \sin^2(y) = 16 (1 - \sin^2(y)) = 16 \cos^2(y)](https://img.qammunity.org/2023/formulas/mathematics/college/cj6qhmmza1wxijkz9w7aq7osawxxjzqx38.png)
Note that we want this substitution to be reversible, so we tacitly assume
. Then
, and
![(16-x^2)^(3/2) = 16^(3/2) \left(\cos^2(y)\right)^(3/2) = 64 |\cos(y)|^3 = 64 \cos^3(y)](https://img.qammunity.org/2023/formulas/mathematics/college/s705d196i8vpddiy0kmpb9se8oflq99rfw.png)
(since
for all real
)
So, the integral we want transforms to
![\displaystyle \int (16 - x^2)^(3/2) \, dx = 64 \int \cos^3(y) * 4\cos(y) \, dy = 256 \int \cos^4(y) \, dy](https://img.qammunity.org/2023/formulas/mathematics/college/fg0c9mj7jvf5ya84mmaayt5pzzmbu6az6i.png)
Expand the integrand using the identity
![\cos^2(x) = \frac{1+\cos(2x)}2](https://img.qammunity.org/2023/formulas/mathematics/college/smdgc8ykyp6taxvglmqwoz6gsso5d14fxu.png)
to write
![\displaystyle \int (16 - x^2)^(3/2) \, dx = 256 \int \left(\frac{1 + \cos(2y)}2\right)^2 \, dy \\\\ = 64 \int (1 + 2 \cos(2y) + \cos^2(2y)) \, dy \\\\ = 64 \int (1 + 2 \cos(2y) + \frac{1 + \cos(4y)}2\right) \, dy \\\\ = 32 \int (3 + 4 \cos(2y) + \cos(4y)) \, dy](https://img.qammunity.org/2023/formulas/mathematics/college/h8o2ks3dxwen0iv96167dqxuyvbn1mwa01.png)
Now integrate to get
![\displaystyle 32 \int (3 + 4 \cos(2y) + \cos(4y)) \, dy = 32 \left(3y + 2 \sin(2y) + \frac14 \sin(4y)\right) + C \\\\ = 96 y + 64 \sin(2y) + 8 \sin(4y) + C](https://img.qammunity.org/2023/formulas/mathematics/college/pbx0z8b9lf4a7fcuchmlvgyeoac06xtmj6.png)
Recall the double angle identity,
![\sin(2y) = 2 \sin(y) \cos(y)](https://img.qammunity.org/2023/formulas/mathematics/college/v5mk0ncgi8sazp1e4z4twubcbf9dwc23ks.png)
![\implies \sin(4y) = 2 \sin(2y) \cos(2y) = 4 \sin(y) \cos(y) (\cos^2(y) - \sin^2(y))](https://img.qammunity.org/2023/formulas/mathematics/college/gys3hsbg3kbetzc0nb2dj5xxu1n324b1p4.png)
By the Pythagorean identity,
![\cos(y) = √(1 - \sin^2(y)) = \sqrt{1 - (x^2)/(16)} = \frac{√(16-x^2)}4](https://img.qammunity.org/2023/formulas/mathematics/college/wf0h83irzf9p45bho02wyiuyu0antw7xot.png)
Finally, put the result back in terms of
.
![\displaystyle \int (16 - x^2)^(3/2) \, dx \\\\ = 96 \sin^(-1)\left(\frac x4\right) + 128 \frac x4 \frac{√(16-x^2)}4 + 32 \frac x4 \frac{√(16-x^2)}4 \left((16-x^2)/(16) - (x^2)/(16)\right) + C \\\\ = 96 \sin^(-1)\left(\frac x4\right) + 8 x √(16 - x^2) + \frac14 x √(16 - x^2) (8 - x^2) + C \\\\ = \boxed{96 \sin^(-1)\left(\frac x4\right) + \frac14 x √(16 - x^2) \left(40 - x^2\right) + C}](https://img.qammunity.org/2023/formulas/mathematics/college/hmr8vwjqgw5bmhhc4qzextrixn7eb6ilyr.png)